The Brain Renin-Angiotensin System Controls Divergent Efferent Mechanisms to Regulate Fluid and Energy Balance - Grobe, Justin L. (2010)
The renin-angiotensin system (RAS), in addition to its endocrine functions, plays a role within individual tissues such as the brain. The brain RAS is thought to control blood pressure through effects on fluid intake, vasopressin release and sympathetic nerve activity (SNA), and may regulate metabolism through mechanisms which remain undefined. We used a double-transgenic mouse model that exhibits brain-specific RAS activity to examine mechanisms contributing to fluid and energy homeostasis. The mice exhibit high fluid turnover through increased adrenal steroids, which is corrected by adrenalectomy and attenuated by mineralocorticoid receptor blockade. They are also hyperphagic but lean because of a marked increase in body temperature and metabolic rate, mediated by increased SNA and suppression of the circulating RAS. β-adrenergic blockade or restoration of circulating angiotensin-II, but not adrenalectomy, normalized metabolic rate. Our data point to contrasting mechanisms by which the brain RAS regulates fluid intake and energy expenditure.